System dynamics modelling for defining livelihood strategies for women smallholder farmers in lowland and upland regions of northern Vietnam: A comparative analysis. (January 2017) - Ha, Tuan M.; Bosch, Ockie J.H.; Nguyen, Nam C.; Trinh, Chung T.
Abstract: This study aims to compare the main determinants of the quality of lives and livelihood options for women smallholder farmers between the lowland and upland regions of northern Vietnam. A systems approach and relevant systems tools were used to develop rich pictures (systems models) that depict the current situations and interrelationships amongst different factors within the systems. The comparative analysis showed similar and distinctive characteristics of the farming systems and women farmers in the two regions. Patterns of relationships and interplays amongst different variables reflect the complexity and multidimensional nature of the lives of the women, who are part of and influenced by the interwoven social, economic, cultural and environmental systems. The study provided insights and practical guidance for making "strategic decisions" towards sustainable agricultural systems and livelihoods of the target group in the respective regions. The systems approach, framework and process steps employed in this study are of a generic nature and can therefore be applied to solve complex problems in various other contexts around the world. Theoretical and practical contributions of using systems approaches in agricultural research and development are discussed. Highlights: Main determinants of lives of women farmers in two northern regions are analysed. System modelling highlights the interwoven relationships of related subsystems. Appropriate strategic decisions for addressing the real local needs are defined. The study addresses current drawbacks in agricultural systems R&D. The approach and process steps can be applied in any context across the world.